(untitled) (Bangladesh Journal of Microbiology, 2016)
Bacteriophages or phages are the viruses that infect bacteria. Phages like all viruses are made up of a nucleic acid core which is surrounded by a protein coat. The majority of phages are known to contain DNA but some contain RNA also. In this study, four salmonella phages were isolated and were subjected to mollecular characterization. All the four Salmonella phages were found to contain DNA as their genetic material. Comparison of protein profiles of phages by SDS-PAGE revealed near identical protein profiles for phages SaP2 and SaP4. Study of storage stability of phage indicated that the titer of the Salmonella phage SaP1 almost remains unaltered during the 14 days storage at different temperatures ranging from - 20oC, 0oC and 4oC. This study shows that the isolated phage have good storage stability. The isolated phages also show narrow host range. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 33-36